Yielding ability of different annual cereal-legume mixtures - Melis R.A.M.; Nieddu D.; Dettori D.; Porqueddu C. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
The preliminary results of a trial aimed at optimizing legume-cereal mixtures are reported. The experiment was carried out during the season 2012-2013 in North Sardinia (Italy). Sixteen plots were sown in November 2012 with pea or vetch and oat or triticale in monoculture and mixtures, following a randomized complete block design with 4 replicates. Measurements included dry matter production, botanical composition and phenology. The dry matter production of sown species ranged between 5.0 and 7.3 t ha-1. Both vetches cultivars showed a very competitive behaviour against unsown species. These preliminary results allowed to identify some mixtures with correct dry matter yield combined with a favourable forage composition and a satisfactory control of unsown species.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)